Effect of exposure to similar flavours in sensory specific satiety: Implications for eating behaviour - González, Ana; Recio, Sergio Andrés; Sánchez, Jesús; Gil, Marta; de Brugada, Isabel (Appetite, 2018)
Sensory-specific satiety (SSS) refers to a decline in pleasantness of eaten foods in comparison to other noningested meals. Although SSS is specific to the eaten food, it can also generalize to other meals that share similar properties to the satiated food. It is possible that this phenomenon could become more specific after extensive experience, as repeated exposure to an assortment of similar food could cause perceptual learning (i.e. an increase in the distinctiveness of each specific item). This in turn would reduce generalization from the consumed food to other similar products, so they will be more readily consumed. To assess this hypothesis, two experiments were carried out using rats as experimental subjects and flavoured solutions as stimuli. In Experiment 1 our main goal was to find the basic SSS effect with two different solutions. As expected, the results showed that rats tended to consume a higher amount of non-sated solutions in comparison to sated ones. Experiment 2 evaluated how repeated exposure to two similar solutions affected generalization of the SSS. Results showed that rats that did not have extensive exposure to the flavoured solutions showed no preference for the non-sated drink. However, rats that had repeated exposure to the flavours showed SSS. The results suggest that easy and continuous access to a high variety of similar unhealthy foods might have long-term effects on food consumption, and highlight a potential mechanism linking obesogenic environments with dietary habits.
Keywords: appetite; obesity; obesogenic environment; perceptual learning; sensory specific satiety; JCR; Scopus